The Relationship Between Mindful Agency and Self-Leadership of Chinese Private College Undergraduates: Mediating Effect of Metacognitive Ability - Chen, Zhaojun; Zhang, Xingxia (Frontiers in Psychology, 2022)
As one of 21st century key skills, self-leadership is not only the internal factor of private college undergraduates’ independent development, but also related to the quality improvement of talent cultivation of private undergraduate colleges. It is proved that mindfulness or metacognition separately has the predictive effect on self-leadership, but their structural relationships has not been revealed. The present study explored the interrelations between mindful agency, metacognitive ability, and self-leadership through the mediation analysis with structural equation modeling, and bootstrapping was conducted to test the mediating effect. The sample comprised 1244 private undergraduate sophomore (38.4% male and 61.6% female), and they completed online questionnaires of mindful agency, metacognitive ability, and self-leadership. The results revealed that mindful agency of private undergraduate students not only directly and positively predicted self-leadership, but also indirectly and positively predicted self-leadership through the mediating effect of metacognitive ability. Metacognitive ability partially mediated the relationship between mindful agency and self-leadership. The direct effect of mindful agency and the mediating effect of metacognitive ability respectively account for 86.9% and 13.1% of the total effect. The results suggest that the more mindful private college undergraduates are, the more willing they are to practise their metacognitive skills in their learning, and the more progress in self-leadership they make. Educational implications for mindfulness training and metacognition practice to foster their self-leadership are discussed.